Vertical Greenery System in urban tropical climate and its carbon sequestration potential: A review - Zaid, Noor Suzaini Mohamed; Perisamy, Eeswari; Hussein, Hazreena; Myeda, Nik Elyna; Zainon, Nurshuhada (Elsevier, 2018)
This article presents a comprehensive literature review of Vertical Greenery System (VGS) in tropical areas, its benefits, its carbon sequestration potential and its calculation methodologies, and its potential for urban heat island (UHI) and climate change mitigation. The contemporary VGS has evolved from the seventh-century beginnings of the Hanging Gardens of Babylon to the vertical urban farms of today in Singapore and Japan. The VGS has demonstrated a significant role in mitigating urban climate change impacts by the potential use of carbon sequestration from vegetation. However, studies on carbon sequestration rate and the methodologies used for calculation are still rather vague. Therefore, this paper reviews existing methodologies for evaluating carbon sequestration rates in tropical climate plants and makes suggestions of potential plants for optimum carbon sequestering.